CSF/plasma HIV-1 RNA discordance even at low levels is associated with up-regulation of host inflammatory mediators in CSF. (July 2016) - Nightingale, Sam; Michael, Benedict D.; Fisher, Martin; Winston, Alan; Nelson, Mark; Taylor, Steven; Ustianowski, Andrew; Ainsworth, Jonathan; Gilson, Richard; Haddow, Lewis; Ong, Edmund; Leen, Clifford; et al.
Highlights: Discordant HIV in CSF is associated with raised inflammatory mediators in CSF. CSF mediators are raised with discordance both at high and low levels. Discordance on ultrasensitive testing can also be also associated with raised mediators. Abstract: Introduction: HIV-1 RNA can be found at higher levels in cerebrospinal fluid (CSF) than in plasma, termed CSF/plasma discordance. The clinical significance of CSF/plasma discordance is not known and the degree of discordance considered important varies. We aimed to determine whether a panel of CSF cytokines, chemokines and associated mediators were raised in patients with CSF/plasma discordance at different levels. Methods: A nested case-control study of 40 CSF samples from the PARTITION study. We used a cytometric bead array to measure CSF mediator concentrations in 19 discordant and 21 non-discordant samples matched for plasma HIV-1 RNA. Discordant samples were subdivided into 'high discordance' (>1log10 ) and 'low discordance' (0.5–1log10, or ultrasensitive discordance). CSF mediators significant in univariate analysis went forward to two-way unsupervised hierarchical clustering based on the patterns of relative mediator concentrations. Results: In univariate analysis 19 of 21 CSF mediators were significantly higher in discordant than non-discordant samples. There were no significant differences between samples with high versus low discordance. The samples grouped into two clusters which corresponded to CSF/plasma discordance (p < 0.0001). In cluster one all mediators had relatively high abundance; this included 18 discordant samples and three non-discordant samples. In cluster two all mediators had relatively low abundance; this included 18 non-discordant samples and one non-discordant sample with ultrasensitive discordance only. Conclusions: CSF/plasma discordance is associated with potentially damaging neuroinflammatory process. Patients with discordance at lower levels (ie. 0.5–1log10 ) should also be investigated as mediator profiles were similar to those with discordance >1log10 . Sensitive testing may have a role to determine whether ultrasensitive discordance is present in those with low level CSF escape.